Improved Li-Ion Cell Construction and Usage Scheme for Achieving Operation Beyond End-of-Life. Issue 9 (1st September 2022) - Aiken, C. P.; Taskovic, T.; Dahn, J. R.
Abstract : Lithium-ion batteries will contribute to the energy storage needs that will enable the widespread implementation of renewable energy alternatives to fossil fuels. Here the role of cell lifetime in achieving sufficient battery deployment to satisfy these needs is discussed in the context of battery manufacturing limitations and the necessity of developing cells with lifetimes beyond those found in contemporary cells. A cell design, and usage scheme reliant on this design, that demonstrates vastly improved lifetime capability is presented, including usage beyond traditional definitions of end-of-life. Specifically, Li[Ni0.5 Mn0.3 Co0.2 ]O2 //graphite cells, a technology that is neither exotic nor innovative, can be built to operate to a low charge voltage limit (3.8 V) and hence contain excess positive electrode capacity. Charging to low voltage naturally reduces the rate of capacity loss and the excess positive electrode capacity functions as a lithium reservoir that can be accessed to counteract capacity loss, both of which combine to yield an incredible lifetime. Specifically, the use of the positive electrode lithium reservoir projects to extend high temperature lifetime at 70 °C by an additional factor of between 1.5 and 10 compared to the lifetime achieved by conventional cycling without accessing this reservoir.